Long-term intestinal failure and home parenteral nutrition: a single center experience - Padinha, Mafalda (2021)
Intestinal failure is the reduction in gut function below the minimum necessary for the absorption of macronutrients and/or water electrolytes. The based treatment for type II and III intestinal failure patients is home parenteral nutrition (HPN) and hydration (HPH). This is a case-series study of HPN/HPH patients of the Hospital Garcia de Orta, Portugal, where thirteen patients present different underlying disorders and various IVS needs of nutrition and/or hydration. Most presented type III failure and most of them survived a long period under HPN and/or HNH.